Method for preparing silicon-aluminum composite tanning agent in aqueous solution
By adjusting the pH value in aqueous solution and mixing silicate and aluminum compound to prepare silicon-aluminum composite tanning agent, the problem of rare raw materials in chrome-free tanning agent preparation and the leather is not resistant to water washing after tanning, and the water washing resistance and softness and plumpness are achieved Leather preparation has the advantages of environmental protection and low cost.
Patent Information
- Application Number
- CN202310689372.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing preparation methods for chrome-free tanning agents have problems such as difficult to obtain raw materials, high cost, many processing steps, and the leather after tanning is not resistant to water washing and easy to detannate. In particular, silicon tanning agents and aluminum tanning agents have poor stability during the water washing process. .
By mixing the silicate solution with the aluminum compound solution in an aqueous solution at a specific ratio, adjusting the pH value to 4.5-5.0, forming a silica gel as a skeleton to fix the aluminum element, and preparing a silicon-aluminum composite tanning agent to avoid the original silicon The repolymerization of acid and the dissolution of aluminum improve the washing resistance of leather.
The leather has achieved significant improvement in the washing resistance performance, and it has not been detanned when washed. The leather is soft and plump, has low cost, and has a wide range of raw materials. It avoids heavy metal pollution and is environmentally friendly.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of leather chemical material preparation, and specifically relates to a method for preparing a silicon-aluminum composite chrome-free tanning agent containing both silicon and aluminum elements in an aqueous solution. Background Art
[0002] Chrome tanning is the only tanning method known so far that uses a single tanning agent to make the shrinkage temperature of finished leather exceed 100°C. Chrome tanned leather not only has good wet heat stability, but also has excellent softness, fullness and water resistance. In addition, chrome tanning is simple to operate and has stable quality. Therefore, chrome tanning is currently the most important tanning method in leather processing. However, although trivalent chromium with tanning properties is used in the chrome tanning process, during the subsequent processing and use of the leather, the trivalent chromium will be oxidized into hexavalent chromium due to the influence of external temperature, pH and light. The toxicity of hexavalent chromium is significantly higher than that of trivalent chromium, and it has clear carcinogenicity and teratogenicity. As domestic and foreign consumers pay more and more attention to health, the hexavalent chromium risks that may be brought by chrome tanned leather have restricted the consumption of leather products, and the production of chrome-free tanned leather has received more and more attention.
[0003] Silicon is the element with a content only lower than oxygen in the earth's crust, and aluminum is the most abundant metal element in the earth's crust. Both of them have a wide range of sources. Studies have shown that both silicon and aluminum have a certain tanning effect and can tan raw hides into leather. However, both silicon tanning agents and aluminum tanning agents have very weak tanning properties. The shrinkage temperature of the finished leather after tanning is generally only about 70°C, and it is very easy to detannage after washing. At present, studies have used silicon and aluminum together to prepare tanning agents. Zhang Hui et al. dissolved silicon compounds and solvents in acid, and then added aluminum compounds to prepare them. After spray drying, chrome-free tanning agents can be obtained (Zhang Hui, Liu Zilong, Wang Xuechuan, Qiang Xihuai. A chrome-free tanning agent and its preparation method, CN 103980304 A). Che Jingtao et al. used organic acids to react with zeolite (containing silicon and aluminum elements) to make the aluminum element in the zeolite produce tanning properties, and obtained silicon-aluminum tanning agents with tanning properties (Che Jingtao, Jin Suyin. A leather tanning treatment method based on zeolite, CN 115232892 A). However, the raw materials required for the above method are not easy to obtain, and organic acids need to be used in the processing process, which is costly. In addition, the preparation process has many steps and is not easy to implement.
[0004] Therefore, developing a preparation technology for silicon-aluminum composite tanning agents with simple process, low cost and wide source of raw materials will provide a new option for the production of chrome-free tanned leather. Summary of the invention
[0005] The reason why leather tanned with aluminum tanning agent is easy to detannage is that aluminum, as an outer track type complex, has a much lower stability with collagen than the complex formed by chromium and collagen. During the process of washing or pickling, water or acid radicals easily replace collagen and combine with aluminum, resulting in detanning. The tanning effect of silicon tanning agent mainly comes from the silicon dioxide generated by the dehydration of orthosilicic acid. Silicon dioxide combines with collagen through multi-point hydrogen bonds. However, orthosilicic acid will repolymerize into a larger spatial network during the static process, making the finished leather hard. At the same time, the multi-point hydrogen bonds between silicon dioxide and collagen are not strong, which makes silicon tanned leather harden during storage and not resistant to water washing. However, silicon and aluminum are the second and third most abundant elements in the earth's crust, and their sources are very wide. In addition, aluminum is a light metal, and its use in tanning completely avoids the problem of heavy metal pollution. In order to solve the problems of silicon tanning agents and aluminum tanning agents, the inventors have conducted in-depth research on the disclosed tanning chemistry, coordination chemistry and silicon tanning and aluminum tanning related materials, and invented a preparation method for silicon-aluminum composite tanning agents.
[0006] Aluminum tanning agent is an outer orbital complex, which is its inherent property and cannot be changed. Therefore, its performance cannot be changed by modifying the traditional inorganic tanning agent, that is, changing the ligand and the central ion. Orthosilicic acid loses water to produce silicon dioxide, and it also has an inherent property to generate a huge spatial network structure over time, which cannot be prevented by changing the external environment. In order to overcome the problems of using silicon tanning agent and aluminum tanning agent separately, the inventor mixed them to prepare a composite tanning agent for use.
[0007] The silicate solution is alkaline, and silicic acid is generated as the pH gradually decreases. After the aluminum compound solution is dissolved in water, it becomes acidic due to the hydrolysis of aluminum. As the pH increases, aluminum hydroxide precipitates are first generated. When the pH continues to increase, the aluminum hydroxide precipitates dissolve to generate metaaluminate. The inventor uses the aluminum compound solution as an acidic substance and drips it into the silicate solution. During this process, the pH of the silicate solution system decreases, and silicate gel is gradually generated. At the same time, aluminum precipitates at this pH to form aluminum hydroxide. The generated silicate gel forms a skeleton to wrap aluminum in it to form a complex. The complex eliminates the original silicate acid in the reaction product, thereby overcoming the defect of hardening of silicon tanned leather. Aluminum is fixed in the silicon skeleton during the reaction, and the water washing resistance of the obtained leather is significantly improved. The shrinkage temperature does not change significantly after washing with clean water for 2 hours, and the appearance and performance of the leather do not change significantly.
[0008] On the basis of the above research, the inventors proposed a method for preparing a silicon-aluminum composite tanning agent in an aqueous solution, characterized in that the preparation method of the silicon-aluminum composite tanning agent comprises the following steps: (1) dissolving a certain amount of silicate in water, wherein the amount of water is 400% of the mass of the silicate, to prepare an alkaline solution; (2) dissolving a certain amount of aluminum compound in water, wherein the amount of water is 300% of the mass of the aluminum compound, to prepare an acidic solution; (3) slowly adding the acidic solution dropwise to the alkaline solution under stirring conditions, and after the addition is completed, adjusting the pH value of the system to 4.5-5.0 with an acidity regulator, continuing to stir for 30 min and then filtering, filtering the obtained precipitate and drying it to obtain the silicon-aluminum composite tanning agent; wherein the molar ratio of Si to Al is 2:1 to 1:2, and the drying temperature of the precipitate is 40-90°C.
[0009] The method for preparing a silicon-aluminum composite tanning agent in an aqueous solution of the present invention is characterized in that the silicate is any one of sodium silicate, sodium silicate nonahydrate or sodium metasilicate. The aluminum compound is any one of aluminum sulfate, aluminum sulfate 18hydrate, aluminum chloride hexahydrate, aluminum triformate or potassium aluminum sulfate dodecahydrate. The acidity regulator is any one of 1 mol / L sodium hydroxide solution or 1 mol / L sulfuric acid solution.
[0010] The molar ratio of Si to Al in the reaction system is 2:1 to 1:2, which ensures that the content of silicon and aluminum is sufficient to form an aluminum compound with silicon as the skeleton. If the silicon content is too high and the aluminum content is too low, the orthosilicic acid in the product cannot be completely eliminated; if the silicon content is too low and the aluminum content is too high, the silicon skeleton cannot completely load the aluminum. Whether it is too much silicon or too much aluminum, the prepared tanning agent will have the defects of silicon tanning agent or aluminum tanning agent, that is, it is not resistant to water washing and hardens during storage.
[0011] The pH of the reaction system directly affects the occurrence of the reaction. If the pH is too high, aluminum tends to produce aluminum hydroxide and cannot be compounded with the silicon skeleton. Although a low pH can ensure the activity of aluminum, silicate is easy to gel, and the efficiency of the loading rate is greatly reduced. The preparation method of a silicon-aluminum composite tanning agent of the present invention is carried out under solid-state reaction, and the pH is also adjusted using solid acid or base, and its amount is 5-15% of the mass of the aluminum compound.
[0012] When the acidic solution is completely added to the alkaline solution, the pH value of the mixed solution is different due to the different raw materials used. When the pH is too low, the aluminum element still exists in the solution in a dissolved state, and the loading rate of the silicon skeleton to aluminum is low; when the pH is too high, the viscosity of the silica gel is large, which is not conducive to the aluminum entering the silicon skeleton to form a complex. Therefore, it is necessary to use an acidity regulator to adjust the system pH to 4.5-5.0. Under this condition, the viscosity of the silica gel is low, and the solubility of aluminum is also small, which is convenient for the formation of a silicon-aluminum complex.
[0013] In order to prevent the silicon-aluminum complex from further reacting to form silicon dioxide and aluminum oxide during the drying process, the drying temperature needs to be controlled at 40-90°C. If the temperature is too low, the drying efficiency will be low and the drying time will be long. If the drying temperature is too high, the silicon-aluminum complex may decompose and lose the tanning effect.
[0014] The preparation method of a silicon-aluminum composite tanning agent provided by the present invention has the following advantages compared with existing products and technologies: 1. The raw materials used are widely available, low in cost, mild in reaction process, simple in operation, and convenient for large-scale production and application; 2. Compared with separate silicon tanning and aluminum tanning, the leather tanned by the silicon-aluminum composite tanning agent prepared by the present invention has excellent water-washing resistance, does not detannage after washing, and has good softness and fullness of the finished leather; 3. The product does not contain formaldehyde, hexavalent chromium, bisphenol compounds, heavy metals and other toxic and harmful ingredients commonly used in leather processing, and is eco-friendly. DETAILED DESCRIPTION
[0015] The following examples are given to illustrate the present invention in more detail. It is necessary to point out that the following examples cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technical personnel skilled in the art based on the above invention content still fall within the scope of protection of the present invention. Example 1
[0016] Dissolve a certain amount of sodium silicate in water, the amount of water used is 400% of the mass of sodium silicate, to prepare an alkaline solution; (2) Dissolve a certain amount of aluminum sulfate 18hydrate in water, the amount of water used is 300% of the mass of aluminum sulfate 18hydrate, to prepare an acidic solution; (3) Slowly add the acidic solution to the alkaline solution under stirring conditions, and after the addition is completed, adjust the pH of the system to 5.0 with 1 mol / L sodium hydroxide solution, continue stirring for 30 min and then filter, filter the resulting precipitate and dry it at 80°C to obtain a silicon-aluminum composite tanning agent; wherein the molar ratio of Si to Al is 1:2. Example 2
[0017] (1) dissolving a certain amount of sodium silicate nonahydrate in water, the amount of water used being 400% of the mass of the sodium silicate nonahydrate, to prepare an alkaline solution; (2) dissolving a certain amount of aluminum sulfate 18hydrate in water, the amount of water used being 300% of the mass of the aluminum sulfate 18hydrate, to prepare an acidic solution; (3) slowly adding the acidic solution dropwise into the alkaline solution under stirring conditions, after the addition is completed, adjusting the pH value of the system to 4.8 with 1 mol / L sodium hydroxide solution, continuing stirring for 30 min and filtering, filtering the obtained precipitate and drying it at 40°C to obtain a silicon-aluminum composite tanning agent; wherein the molar ratio of Si to Al is 1:1. Example 3
[0018] (1) dissolving a certain amount of sodium metasilicate in water, the amount of water used being 400% of the mass of the sodium metasilicate, to prepare an alkaline solution; (2) dissolving a certain amount of aluminum sulfate in water, the amount of water used being 300% of the mass of the aluminum sulfate, to prepare an acidic solution; (3) slowly adding the acidic solution dropwise into the alkaline solution under stirring conditions, after the addition is completed, adjusting the pH value of the system to 4.5 with 1 mol / L sulfuric acid solution, continuing stirring for 30 min and filtering, filtering the obtained precipitate and drying it at 90°C to obtain a silicon-aluminum composite tanning agent; wherein the molar ratio of Si to Al is 2:1. Example 4
[0019] (1) dissolving a certain amount of sodium silicate nonahydrate in water, the amount of water used being 400% of the mass of the sodium silicate nonahydrate, to prepare an alkaline solution; (2) dissolving a certain amount of aluminum chloride hexahydrate in water, the amount of water used being 300% of the mass of the aluminum chloride hexahydrate, to prepare an acidic solution; (3) slowly adding the acidic solution dropwise into the alkaline solution under stirring conditions, after the addition is completed, adjusting the pH value of the system to 4.6 with 1 mol / L sulfuric acid solution, continuing stirring for 30 min and filtering, filtering the obtained precipitate and drying it at 60°C to obtain a silicon-aluminum composite tanning agent; wherein the molar ratio of Si to Al is 1.5:1. Example 5
[0020] Dissolve a certain amount of sodium silicate in water, the amount of water used is 400% of the mass of sodium silicate nonahydrate, to prepare an alkaline solution; (2) Dissolve a certain amount of aluminum triformate in water, the amount of water used is 300% of the mass of aluminum triformate, to prepare an acidic solution; (3) Slowly add the acidic solution to the alkaline solution under stirring conditions, and after the addition is completed, adjust the pH of the system to 4.9 with 1 mol / L sodium hydroxide solution, continue stirring for 30 minutes and then filter, filter the resulting precipitate and dry it at 80°C to obtain a silicon-aluminum composite tanning agent; wherein the molar ratio of Si to Al is 1:1.5. Example 6
[0021] (1) dissolving a certain amount of sodium metasilicate in water, the amount of water used being 400% of the mass of sodium metasilicate, to prepare an alkaline solution; (2) dissolving a certain amount of potassium aluminum sulfate dodecahydrate in water, the amount of water used being 300% of the mass of potassium aluminum sulfate dodecahydrate, to prepare an acidic solution; (3) slowly adding the acidic solution dropwise into the alkaline solution under stirring conditions, after the addition is completed, adjusting the pH value of the system to 4.5 with 1 mol / L sodium hydroxide solution, continuing stirring for 30 min and filtering, filtering the obtained precipitate and drying it at 70°C to obtain a silicon-aluminum composite tanning agent; wherein the molar ratio of Si to Al is 1:1. Example 7
[0022] (1) dissolving a certain amount of sodium silicate nonahydrate in water, the amount of water used being 400% of the mass of the sodium silicate nonahydrate, to prepare an alkaline solution; (2) dissolving a certain amount of potassium aluminum sulfate dodecahydrate in water, the amount of water used being 300% of the mass of the potassium aluminum sulfate dodecahydrate, to prepare an acidic solution; (3) slowly dropping the acidic solution into the alkaline solution under stirring conditions, after the dropping is completed, adjusting the pH of the system to 4.7 with 1 mol / L sodium hydroxide solution, continuing stirring for 30 min and filtering, filtering the obtained precipitate and drying it at 60°C to obtain a silicon-aluminum composite tanning agent; wherein the molar ratio of Si to Al is 1:1.
Claims
1. A method for preparing a silicon-aluminum composite tanning agent in an aqueous solution, characterized in that The preparation method of the silicon-aluminum composite tanning agent comprises the following steps: (1) dissolving a certain amount of silicate in water, wherein the amount of water used is 400% of the mass of the silicate, to prepare an alkaline solution; (2) dissolving a certain amount of aluminum compound in water, wherein the amount of water used is 300% of the mass of the aluminum compound, to prepare an acidic solution; (3) slowly dropping the acidic solution into the alkaline solution under stirring conditions, and after the dropping is completed, adjusting the pH value of the system to 4.5-5.0 with an acidity regulator, continuing stirring for 30 minutes and then filtering, filtering the obtained precipitate and drying it to obtain the silicon-aluminum composite tanning agent; wherein the molar ratio of Si to Al is 2:1 to 1:2, and the drying temperature of the precipitate is 40-90°C.
2. A method for preparing a silicon-aluminum composite tanning agent in an aqueous solution, characterized in that The silicate is any one of sodium silicate, sodium silicate nonahydrate or sodium metasilicate.
3. A method for preparing a silicon-aluminum composite tanning agent in an aqueous solution, characterized in that The aluminum compound is any one of aluminum sulfate, aluminum sulfate 18hydrate, aluminum chloride hexahydrate, aluminum triformate, or aluminum potassium sulfate dodecahydrate.
4. A method for preparing a silicon-aluminum composite tanning agent in an aqueous solution, characterized in that The acidity regulator is any one of 1 mol / L sodium hydroxide solution or 1 mol / L sulfuric acid solution.
Citation Information
Patent Citations
Tanning process
CA416724A
Chromium-free tanning agent and preparation method thereof
CN103980304A
Preparation method and application of organic and inorganic complexing and tanning agent
CN106676210A
Metod of manufacturing for Aluminium silicate soltes
KR1020020039274A
